Peran Kepemimpinan Perempuan dalam Pengembangan Manajemen Pendidikan Islam : The Role of Women's Leadership in the Development of Islamic Education Management - Latifah, Hilmiyatul; Asy’ari, Hasyim (Thawalib: Jurnal Kependidikan Islam, 2024)
The aim of this research is to analyze and describe the role of female leadership in the development of Islamic education management. The research methodology is qualitative with a library study approach. Data collection was carried out by searching for and gathering articles from field research or literature that have been published in journals using Google Scholar. Data processing involved condensing the article results according to the topic, which was then presented in the form of narrative and tables, followed by drawing conclusions to obtain the latest insights from the articles. The results of the research show that female leadership in Islamic education has a significant impact on improving the quality of madrasahs. Female school principals apply discipline, professionalism, and good communication to improve teacher performance and the quality of education, despite challenges such as limited budgets. Leadership based on collaboration and empathy has proven effective in enhancing student achievement and human resource quality. Democratic, charismatic, and servant leadership styles contribute to the development of the organization and school culture. Despite facing gender stereotypes, female leadership is recognized as competent and nurturing, helping to change negative perceptions and strengthen the empowerment of women in the Islamic perspective.